A prospective study of psychiatric disorder and cognitive function in systemic lupus erythematosus. Issue 5 (May 1994) - Hay, E M; Huddy, A; Black, D; Mbaya, P; Tomenson, B; Bernstein, R M; Lennox Holt, P J; Creed, F
Abstract : OBJECTIVES--To investigate change in psychiatric disorder and change in cognitive function in patients with systemic lupus erythematosus (SLE) assessed on two occasions two years apart. METHODS--A prospective cohort study of 49 patients with SLE using standardised psychiatric and clinical research methods. RESULTS--The point prevalence of psychiatric disorder (20% and 24%), and of cognitive impairment (23% and 18%), was similar at first and second interview for the whole group. There was, however, considerable change in individual patient's psychiatric status and cognitive function: only 1/9 patients with impairment on two or more cognitive tests at first interview was still impaired at second interview. Change in cognitive function appeared to mirror change in psychiatric status. CONCLUSIONS--These findings suggest that the previously reported high prevalence of cognitive impairment in SLE may be explained by coexisting psychiatric disorder, rather than reflecting subclinical central nervous system (CNS) involvement.